2017
DOI: 10.1159/000479814
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Hemi-/Laminectomy and Facetectomy Approach for the Treatment of Dumbbell-Shaped Schwannomas in the Subaxial Cervical Spine: A Retrospective Study of 26 Cases

Abstract: Objective: It is difficult to completely and safely remove a tumor that is located in the subaxial cervical spine by using the posterior approach because of the anatomical characteristics. Previous reports regarding the total removal of subaxial schwannomas using the one-stage posterior approach are still limited. This study was to evaluate the feasibility and efficacy of treating the dumbbell-shaped schwannomas in the subaxial cervical spine using the one-stage posterior approach. Methods: Patients with dumbb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…However, no significant differences were detected between the 2 groups in JOA-T score or JOA-L score. The neurological function was much improved, which is not only indicated by most patients being very satisfied with their treatment results, but is also in line with some previous reports that documented the improvements caused by laminectomy with or without internal fixation [4,30]. Here, it cannot be neglected that there is a close correlation between functional scores and radiographic parameters, including sagittal balance parameters [31,32].…”
Section: Discussionsupporting
confidence: 87%
“…However, no significant differences were detected between the 2 groups in JOA-T score or JOA-L score. The neurological function was much improved, which is not only indicated by most patients being very satisfied with their treatment results, but is also in line with some previous reports that documented the improvements caused by laminectomy with or without internal fixation [4,30]. Here, it cannot be neglected that there is a close correlation between functional scores and radiographic parameters, including sagittal balance parameters [31,32].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, to expose a dumbbell tumor originating from the nerve root during surgery, it is necessary to resect the whole or part of the lateral mass. [15] In addition, primary spinal tumors often directly involve the lateral mass, and their treatment even requires total en bloc spondylectomy (including the vertebral body, lateral mass, lamina, transverse process, and other structures). In addition, infection and trauma may lead to bone destruction of lateral masses.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that a combined anterior and posterior approaches only be performed when there is residual tumor, but this suggestion was not widely accepted by patients and required a long surgical time 14 . However, the posterior approach is popular and safe and has a low potential for damaging important structures.…”
Section: Discussionmentioning
confidence: 99%
“…However, the posterior approach is popular and safe and has a low potential for damaging important structures. As long as the VA can be visualized and protected, a one-stage posterior approach can be performed and even extended to the ventral side of the vertebral artery 14 . For these reasons, we prefer the posterior approach for our patients.…”
Section: Discussionmentioning
confidence: 99%